Protection of soil and water from pollution runoff airports: environmental and legal requirements - Тимкович, Ірина Іванівна; Кальницька, Діана Дмитрівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2016)
The authors note that the airport is an important component of infrastructure of transport system of Ukraine because it is directed to the receipt and dispatch of aircraft, passengers, baggage, mail and cargo, maintenance and flight crews. The operation of airports provides for the following types of economic and technological activities (operation of aircraft and ground equipment, accompanied by exhaust gases and products of combustion of aviation fuels, their deposition on soil and surface production, washing and processing of aircraft, runways, tools, icing, maintenance in good condition of maintenance base, navigation structures, outbuildings, and hygiene needs of the passenger service in accordance with hygienic requirements, etc.) that cause land pollution and water effluents from a variety of mechanical, physical and chemical impurities (residue, chips , dirt, sand, oil, benzene, lead, etc.), the negative impact on certain natural features of the ecological system as a whole, endangering people’s health. Therefore, among the relevant issues that needs to be a comprehensive solution remains relevant to the protection of contamination of soil and water from sewage airports. The article characteristic analyzes of environmental requirements and standards regulations that define the direction and ways to protect soil and water pollution from runoff airports. The authors suggest that comprehensive application of appropriate measures is an important constituent factor in ensuring the environmental safety of airports, will contribute to minimizing the negative effects on the environment.